2018
DOI: 10.1001/jamafacial.2018.0165
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Temporal Hollowing Augmentation by Targeted Volume Restoration of Fat Compartments in Chinese Adults

Abstract: IMPORTANCE Previous anatomical and clinical studies have suggested that targeted restoration of the volume and distribution of fat compartments using appropriate cannula entry sites and injection planes is an excellent fat-grafting technique for facial contouring and hand rejuvenation. OBJECTIVE To perform subjective and objective evaluations of the safe and effective profile of the targeted fat-grafting technique for temporal hollowing augmentation. DESIGN, SETTING, AND PARTICIPANTS In a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
(61 reference statements)
0
26
0
Order By: Relevance
“…Based on these considerations and anatomic studies in the temporal region, 5 midiface, 6 and hand, 7 the authors developed a concept of targeted fat grafting technique, which advocates targeted restoration of physiologic distribution and volume of fat compartments using anatomically adequate cannula entry sites and injection planes. The authors' previous clinical studies have demonstrated effective and safety profiles in facial contouring, 6 temporal hollowing augmentation, 5,8 and hand rejuvenation 7 and suggested more applications in other regions.…”
Section: Introductionmentioning
confidence: 97%
“…Based on these considerations and anatomic studies in the temporal region, 5 midiface, 6 and hand, 7 the authors developed a concept of targeted fat grafting technique, which advocates targeted restoration of physiologic distribution and volume of fat compartments using anatomically adequate cannula entry sites and injection planes. The authors' previous clinical studies have demonstrated effective and safety profiles in facial contouring, 6 temporal hollowing augmentation, 5,8 and hand rejuvenation 7 and suggested more applications in other regions.…”
Section: Introductionmentioning
confidence: 97%
“…In all, the fat grafting retention rates varied from 21.0% to 82.3% with 3- to 36-month follow-up periods. Among these articles, some studies [17,2025] were designed to collect follow-up data at unified time points, commonly 3, 6, and/or 12 months. For these studies, we tried to list the measurement data of the unified points of time to better analyze the fat grafting retention rates among the different fat-processing techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al's anatomic study demonstrated four fat compartments in the temporal region ideal for fat grafting . This was followed up by a study looking at 142 autologous fat grafts with both subjective improvement as well as clinical improvement of two grades on average based on the Hollowness Severity Rating Scale …”
Section: Discussionmentioning
confidence: 99%